Paternal Resistance Exercise Modulates Skeletal Muscle Remodeling Pathways in Fathers and Male Offspring Submitted to a High-Fat Diet - Salomão, Rebecca (2021)
Although some studies have shown that a high-fat diet (HFD) adversely affects muscle extracellular matrix remodeling, the mechanisms involved in muscle trophism, inflammation, and adipogenesis have not been fully investigated. Thus, we investigated the effects of 8 weeks of paternal resistance training (RT) on gene and protein expression/activity of critical factors involved in muscle inflammation and remodeling of fathers and offspring (offspring exposed to standard chow or HFD). Animals were randomly distributed to constitute sedentary fathers (SF; n = 7; did not perform RT) or trained fathers (TF n = 7; performed RT), with offspring from mating with sedentary females. After birth, 28 male pups were divided into four groups (n = 7 per group): offspring from sedentary father submitted either to control diet (SFO-C) or high-fat diet (SFO-HF) and offspring from trained father submitted to control diet (TFO-C) or high-fat diet (TFO-HF). Our results show that an HFD downregulated collagen mRNA levels and upregulated inflammatory and atrophy pathways and adipogenic transcription factor mRNA levels in offspring gastrocnemius muscle. In contrast, paternal RT increased MMP-2 activity and decreased IL-6 levels in offspring exposed to a control diet. Paternal RT upregulated P70s6k and Ppara mRNA levels and downregulated Atrogin1 mRNA levels, while decreasing NFκ-B, IL-1β, and IL-8 protein levels in offspring exposed to an HFD. Paternal physical training influences key skeletal muscle remodeling pathways and inflammatory profiles relevant for muscle homeostasis maintenance in offspring submitted to different diets.